The Islamic Country Nigeria Borrows on Riba: Introducing Esham as an Instrument of Borrowing - Saidu, Oluwaseun S.; Cizakca, Murat; Alhabshi, Syed Othman (International Journal of Islamic Economics and Governance, 2025)
The Nigerian government continues to adopt conventional financial instruments of government borrowing. The use of these instruments both in the past and in the present has not yielded the desired results as it continues to wallow in debt with little or no development to show for it. This borrowing escapade by the government would not have been problematic if Nigeria were a religiously neutral state. However, Nigeria is home to over a hundred million Muslims and her constitution guarantees freedom of religion whilst she regularly sponsors pilgrimages to the haramain and sharafain every year. It is therefore visible to the blind and audible to the deaf that Nigeria is an Islamic country and therefore should use Islamic instruments of borrowing. The objective of this paper is to highlight the abhorrent use of non-Islamic means of borrowing by the Nigerian Government and to introduce a relatively new instrument of borrowing for use within the Nigerian state. The benefit of using an Islamic means of borrowing therefore becomes evident in that, the overarching maqsad of the shari’ah being obedience to Allah, blessings from the heavens and the earth will naturally trickle in (The Qur’an, 7: 96) This is not withstanding the concomitant pragmatic and pecuniary benefits associated with non-usurious transactions. Methodically, the paper adopts legal reasoning, scriptural reasoning, constitutional analysis and public evidence.